Physicochemical Characterization and Recyclability of CaO/SiO₂ Catalysts Derived from Eggshell and Rice Husk for Biodiesel Application - Nurhana, Eti Ayu; Perdani, Meka Saima; Umam, Hilman Imadul; Fadilla, Amalia Dian; Sitanggang, Christin Octaviani (Indonesian Journal of Chemical Research, 2025)
This study aims to evaluate the physicochemical characteristics and reusability of CaO/SiO₂ heterogeneous catalysts synthesized from eggshell and rice husk waste for biodiesel production. The catalyst, prepared with a 2:1 CaO to SiO₂ ratio, was applied in three transesterification cycles using waste cooking oil. Between cycles, the used catalyst was washed with n-hexane and dried at 80 °C for 12 hours. Catalyst characterization was performed using SEM-EDX, FTIR, and N2 adsorption-desorption analysis. The biodiesel yield decreased from 65 ± 4.95% (first cycle) to 54 ± 1.41% and 46 ± 2.12% in subsequent cycles, indicating reduced catalytic activity. SEM-EDX revealed particle agglomeration, calcium content declined (from 24.78% to 19.22%), and increased silicon exposure (from 4.66% to 21.86%). FTIR analysis detected organic residue accumulation, while N2 adsorption-desorption results showed a decrease in surface area (20.79 to 11.67 m²/g) and pore volume (0.03 to 0.02 cc/g), with increased pore size. The biodiesel showed a density of 1112–1119 ± 1.41 kg/m³ and a kinematic viscosity of 2.03–2.07 cSt, indicating it still requires purification to meet SNI 7182:2015 standards. These findings highlight the catalyst's promising initial performance and underscore the need for regeneration strategies to maintain catalytic efficiency over multiple uses.